Patient-Reported Convalescence and Quality of Life Recovery: A Comparison of Open and Robotic-Assisted Radical Cystectomy. (December 2016) - Li, Amy Y.; Filson, Christopher P.; Hollingsworth, John M.; He, Chang; Weizer, Alon Z.; Hollenbeck, Brent K.; Gilbert, Scott M.; Hafez, Khaled S.; Lee, Cheryl T.; Dunn, Rodney L.; Montgomery, Jeffrey S.
Background . Robotic-assisted radical cystectomy (RARC) is gaining traction as a surgical approach, but there are limited data on patient-reported outcomes for this technique compared to open radical cystectomy (ORC). Objective . To compare health-related quality of life (HRQoL) and short-term convalescence among bladder cancer patients who underwent ORC and RARC. Methods . Review of a single-institution bladder cancer database was conducted. Baseline and postoperative HRQoL was evaluated using the Bladder Cancer Index (BCI) for 324 patients who had ORC (n = 267) or RARC (n = 57) between 2008 and 2012. The BCI assesses function and bother in urinary, bowel, and sexual domains. Among 87 distinct patients (ORC n = 67, RARC n = 20), we also evaluated short-term postoperative convalescence using the Convalescence and Recovery Evaluation (CARE) questionnaire. Our primary outcomes were HRQoL within 12 months and short-term convalescence within 6 weeks following cystectomy. We fit generalized estimating equation regression models to estimate longitudinal changes in BCI scores within domains, and CARE domain score differences were tested with Wilcoxon rank-sum tests. Results . Clinical characteristics and baseline BCI/CARE scores were similar between the 2 groups (all P > .05). Within 1 year after surgery, recovery of HRQoL across all BCI domains was comparable, with scores nearly returning to baseline at 1 year for all patients. CARE scores at 4 weeks revealed that patients treated with ORC had better pain (29.1 vs 20.0, P = .02) domain scores compared to RARC. These differences abated by week 6. Conclusions . HRQoL recovery and short-term convalescence were similar in this cohort following ORC and RARC.